Process and outcomes of telephone reassurance program training for older adult volunteers. Issue 1 (2nd January 2021) - Lee, Kathy; Fields, Noelle L.; Cassidy, Jessica; Feinhals, Gretchen
ABSTRACT: The purpose of this study was to examine the experience of Senior Companions with telephone reassurance program training delivered via Zoom and the feasibility of using teleconferencing as a platform for training older adult volunteers during the COVID-19 pandemic. Volunteers were recruited from a local Senior Companion Program. We assessed training enrollment and participation rates. We also examined the overall participant experience with the program training by asking structured/semi-structured questions and analyzed the data using content analysis. The average age of the volunteers was 72.5 (n=20). During the first recruitment, 39 Senior Companions expressed their interest in the program. As a result, 20 out of 39 volunteers (51.3%) successfully completed the teleconference training (18 joined over the phone & 2 joined online). Findings from this pilot study suggest that the teleconferencing training was feasible for older adult volunteers and the volunteers discussed that the program training would benefit and support their volunteer roles. The findings of this study provide insight for gerontological researchers and educators related to potential strategies for completing research and training in the midst of COVID-19. The use of teleconferencing training that incorporates best practices for older adults' learning may offer promise for the potential scalability and sustainability of volunteer trainings during and after COVID-19.